The Role of Gut Microbiota in Metabolism, Immune Response, and Metabolic Health - Yusfarani, Delia; Hasanah, Uswatun; Raharjeng, Anita Restu Puji; Saputra, Andi; Saputra, Muhammad Alif; Mauludi, Ikhwan Hafizh; Yap, Kenny Edward (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2025)
The gut microbiota, a community of microorganisms residing in the digestive tract, plays a crucial role in human health, particularly in regulating immune function and metabolism. This study aims to explore the contributions of the gut microbiota to immune responses and metabolic health, as well as its role in preventing chronic diseases. Through a literature review approach, an analysis was carried out regarding the latest findings of the role of microbiota in producing metabolites such as short-chain fatty acids (SCFAs), which act as anti-inflammatory agents and strengthen mucosal integrity. A balanced gut microbiota helps regulate immune function, inhibit pathogen colonization, and support overall metabolic health. However, lifestyle factors such as high-sugar, low-fiber diets, antibiotic misuse, stress, and inadequate sleep can disrupt this microbial balance, often leading to dysbiosis. Dysbiosis, or an imbalance in gut microbiota, may trigger metabolic and inflammatory disorders, including diabetes, autoimmune diseases, and cardiovascular conditions. This study underscores the importance of maintaining a balanced gut microbiota for disease prevention and long-term health promotion, as well as raising awareness about the impact of lifestyle choices on gut health.